An investigation of anatomical competence in junior medical doctors. Issue 1 (27th February 2015) - Vorstenbosch, Marc A.T.M.; Kooloos, Jan G.M.; Bolhuis, Sanneke M.; Laan, Roland F.J.M.
Abstract : Because of a decrease of the time available for anatomy education, decisions need to be made to reduce the relevant content of the anatomy curriculum. Several expert consensus initiatives resulted in lists of structures, lacking analysis of anatomical competence. This study aims to explore the use of anatomical knowledge by medical doctors in an attempt to delineate the nature of anatomical competence. The research question is: what kind of anatomical knowledge do junior medical doctors use during a consultation with a patient presenting with a shoulder complaint? Ten junior medical doctors participated in this stimulated recall study. Each of them was videotaped while performing a consultation with a standardized patient with a complex shoulder complaint. The recording was viewed immediately after. Participants were videotaped again while verbalizing the thoughts they remembered having during the consultation. Verbatim transcriptions were coded by two coders using the qualitative data analysis ATLAS.ti software. Results were that these junior medical doctors used anatomical knowledge in all phases of the consultation, especially during physical examination. The use of anatomical terms was strongly associated with clinical reasoning and it was apparent that every subject visualized relevant anatomical information. Conclusion is that young medical doctors actively use their anatomical knowledge and it seems that the relevant anatomy consists largely of adequate visual representations in memory. Anatomy teachers should focus the students' learning activity on building an adequate visual representation of anatomical structures. This should be supported by assessments that test the quality of the students' visual representations. Anat Sci Educ. © 2015 American Association of Anatomists.